The divided earth - Hicks, Faith Erin (Hicks, Faith Erin. Nameless city (Series), 2018)
In the Nameless City held by rogue Dao prince Erzi and his forces, a coalition of Dao and Yisun forces are determined to end the war, whatever the cost, and the people, called the Named, are caught in the middle. Meanwhile, Kai and Rat have to find a way to sneak into the palace to recover an ancient and deadly formula for the weapon of mass destruction, the "napatha," that Erzi has unearthed, before Erzi has a chance to use it.